Antenatal care in rural Bangladesh: current state of costs, content and recommendations for effective service delivery - Jo, Youngji; Alland, Kelsey; Ali, Hasmot; Mehra, Sucheta; LeFevre, Amnesty E.; Pak, Semee (Esther); Shaikh, Saijuddin; Christian, Parul; Labrique, Alain B. (BMC health services research, 2019)
Background Measurement of antenatal care (ANC) service coverage is often limited to the number of contacts or type of providers, reflecting a gap in the assessment of quality as well as cost estimations and health impact. The study aims to determine service subcomponents and provider and patient costs of ANC services and compares them between community (i.e. satellite clinics) and facility care (i.e. primary and secondary health centers) settings in rural Bangladesh. Methods Service contents and cost data were collected by one researcher and four interviewers in various community and facility health care settings in Gaibandha district between September and December 2016. We conducted structured interviews with organization managers, observational studies of ANC service provision ( n = 70) for service contents and provider costs (service and drug costs) and exit interviews with pregnant women ( n = 70) for patient costs (direct and indirect costs) in health clinics at community and facility levels. Fisher’s exact tests were used to determine any different patient characteristics between community and facility settings. ANC service contents were assessed by 63 subitems categorized into 11 groups and compared within and across community and facility settings. Provider and patient costs were collected in Bangladesh taka and analyzed as 2016 US Dollars (0.013 exchange rate). Results We found generally similar provider and patient characteristics between the community and facility settings except in clients’ gestational age. High compliance (> 50%) of service subcomponents were observed in blood pressure monitoring, weight measurement, iron and folate supplementation given, and tetanus vaccine, while lower compliance of service subcomponents (< 50%) were observed in some physical examinations such as edema and ultrasonogram and routine tests such as blood test and urine test. Average unit costs of ANC service provision were about double at the facility level ($2.75) compared with community-based care ($1.62). ANC patient costs at facilities ($2.66) were about three times higher than in the community ($0.78). Conclusion The study reveals a delay in pregnant women’s initial ANC care seeking, gaps in compliance of ANC subcomponents and difference of provider and patient costs between facility and community settings.